2007
DOI: 10.1111/j.1365-2249.2007.03357.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal and peripheral immune responses to chlamydial heat shock proteins in women infected with Chlamydia trachomatis

Abstract: SummaryMost of the studies on 60-kDa and 10-kDa chlamydial heat shock proteins (HSPs) to date have been carried out with blood lymphocytes or serum antibody responses, which do not provide a clear picture of the actual pathogenesis as they do not differentiate primary infection from recurrent infection. Thus, in the present study induction of the immune response was evaluated by studying lymphoproliferation of both cervical and peripheral lymphocytes to synthetic peptides of cHSP60, cHSP10 and major outer memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
(37 reference statements)
2
35
0
1
Order By: Relevance
“…IL-17 and IL-22 were five and three times as high in the cervical secretions of C. trachomatis-positive women (n ϭ 27) as in negative controls (n ϭ 17) (50). Titers of IgG and IgA antibodies to C. trachomatis EBs were higher in the cervical washes of C. trachomatis-positive fertile women during primary infection than during recurrent infection (49). However, the cervical titer of IgG to specific chlamydial antigens (cHSP60 and cHSP10) was higher in a recurrent infection than in a primary infection, which is what would be expected (49).…”
Section: Immune Responses From Reproductive Sites and Tissuesmentioning
confidence: 85%
See 2 more Smart Citations
“…IL-17 and IL-22 were five and three times as high in the cervical secretions of C. trachomatis-positive women (n ϭ 27) as in negative controls (n ϭ 17) (50). Titers of IgG and IgA antibodies to C. trachomatis EBs were higher in the cervical washes of C. trachomatis-positive fertile women during primary infection than during recurrent infection (49). However, the cervical titer of IgG to specific chlamydial antigens (cHSP60 and cHSP10) was higher in a recurrent infection than in a primary infection, which is what would be expected (49).…”
Section: Immune Responses From Reproductive Sites and Tissuesmentioning
confidence: 85%
“…Titers of IgG and IgA antibodies to C. trachomatis EBs were higher in the cervical washes of C. trachomatis-positive fertile women during primary infection than during recurrent infection (49). However, the cervical titer of IgG to specific chlamydial antigens (cHSP60 and cHSP10) was higher in a recurrent infection than in a primary infection, which is what would be expected (49). Flow cytometric analysis of lymphocytes present at the cervixes of C. trachomatis-infected women identified the increased presence of a unique cell type, ␣4␤7 ϩ CLA ϩ memory T cells (51).…”
Section: Immune Responses From Reproductive Sites and Tissuesmentioning
confidence: 91%
See 1 more Smart Citation
“…Cohen et al, (2005) found that select peripherical blood mononuclear cell lymphoproliferative responses to Chlamydia EBS and heat shock protein 60 (cHSP60) correlated with protection against incident Chlamydia but not with a reduction in incident chlamydial infection. Cervical lymphoproliferative response to cHSP10 were higher in reccurent infection, while lymphoproliferative response to OmpA was higher in primary infection (Agrawal et al, 2007). The presence of OmpA A type E protein favour the persistence of infection at 1 year follow up (Morre et al, 2002), as well as infection load (a quantitative measure of persistence organism burden and pressumably a surogate for Chlamydia trachomatis replication.…”
Section: Veenemans Et Al(2002) Evaluated Hsg and Igg Formentioning
confidence: 92%
“…119 It has also been reported that the levels of IFN-γ were significantly higher in the cervical washes of women with recurrent chlamydial infection, as compared to the cytokine levels from women with primary chlamydial genital infections. 120 In a recent study of 250 women, 59 of whom had TFI, C. trachomatis-infected cells produced significantly higher levels of the IL-12B subunit, p40 than uninfected cells, providing evidence that genetic variation in the IL-12 cytokine family affects C. trachomatis-specific immune responses. 121 Finally, as noted by Mabey et al, "an important difference between ocular and genital infection is that in the eye the damaging sequelae occur at the site of infection, the conjunctival epithelium" while "by contrast in the female genital tract, the major sequelae develop in the fallopian tubes and not at the cervix, which is the site of inoculation".…”
Section: Acquired Immunity and Pathologymentioning
confidence: 99%